Communities Moving Ahead, Falling Behind: Evidence from the Index of Deep Disadvantage. Issue 1 (May 2021) - Fusaro, Vincent A.; Shaefer, H. Luke; Simington, Jasmine
Using a multidimensional index weighting factors related to income, health, and social mobility—the Index of Deep Disadvantage (IDD)—we rank the well-being of disadvantaged U.S. counties (initial scores below the median IDD) when they were on the cusp of the Great Recession and then again well into the recovery. We compare the characteristics of counties that saw improvements to those that saw declines. We find that a clear majority of counties were stable in relative rank. Counties showing improvement tended to have been worse off prerecession than counties where well-being declined. Improving counties were less likely to be urban, tended to have smaller fractions of the population identifying as Black and larger fractions as white, and had a lower proportion of jobs in manufacturing. Stable counties were, on average, the worst off pre-recession and thus remained the worst off near the end of the recovery. All county groups improved in income and employment through the recovery, but these advances were not consistently associated with gains in other areas such as incidence of low-weight births.